Understanding the dynamics of keratin weakening and hydrolysis by proteases - Navone, Laura (PLoS One, 2018)
Keratin is the structural protein in hair, nails, feathers and horns. Keratin is recalcitrant, highly disulfide bonded and is generally inaccessible to common proteases. Only certain types of proteases, called keratinases, are able to cleave the peptide bonds within the keratin structure. Due to this outstanding activity, keratinases have potential application in industries such as livestock, cosmetics and pharmaceuticals. Yet, the process of enzymatic keratin degradation is poorly understood, affecting the development of industrial enzyme formulations that may require full or only partial modification or weakening. Here we investigate the dynamics of keratin weakening and hydrolysis, showing that the decrease in hair mechanical strength is associated with cuticle removal and damage to the cortex and complete breakdown is dependent on reducing agents. Proteases with keratinolytic activity were selected and applied to hair with degradation examined by mechanical, biochemical and microscopic techniques. The extent of keratin degradation was highly enhanced by the presence of reducing agents, principally sodium thioglycolate, exceeding 90% degradation within 16 h of enzymatic treatment. Application was extended to feathers showing that the findings are relevant to improving the use of keratinases in a variety of industries. Overall, the outcomes provide valuable insights into the keratin degradation process by enzymes for the optimization of cosmetic and pharmaceutical products and for livestock waste recycling among other important applications.